1982
DOI: 10.1007/bf00257728
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous glibenclamide investigated by a high performance liquid Chromatographic assay

Abstract: A simple high performance liquid chromatographic assay for the determination of plasma glibenclamide concentrations is described. This resolved glibenclamide from normal plasma constituents. The calibration curve of the assay was linear over the range 10-500 microgram/l and the minimum level of detection was 2 microgram/l. Within-assay coefficients of variation were 11.6% (20 microgram/l); 5.3% (50 microgram/l); 6.8% (100 microgram/l); between-assay coefficients of variation were 8.4% (20 microgram/l); 4.7% (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…First, differing brands of glibenclamide have often been used and there is evidence that formulation may significantly affect bioavailability of the drug (Arnquist et al, 1983;Chalk et al, 1986;McEwen, 1984;Rupp et al, 1972). Some have studied glibenclamide entering the circulation so quickly that a rapid distribution phase could be confused with a first elimination half-life (Rogers et al, 1982). Second, some have studied normal subjects (Ings et al, 1981;Neugebauer et al, 1985;Sartor et al, 1980b), whilst others have, like ourselves, studied diabetic patients (Matsuda et al, 1983;Sartor et al, 1982) and the question may be raised as to whether the observed variations in drug handling reflect alterations in gastrointestinal motility secondary to autonomic neuropathy complicating the diabetic state (Ikegami et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, differing brands of glibenclamide have often been used and there is evidence that formulation may significantly affect bioavailability of the drug (Arnquist et al, 1983;Chalk et al, 1986;McEwen, 1984;Rupp et al, 1972). Some have studied glibenclamide entering the circulation so quickly that a rapid distribution phase could be confused with a first elimination half-life (Rogers et al, 1982). Second, some have studied normal subjects (Ings et al, 1981;Neugebauer et al, 1985;Sartor et al, 1980b), whilst others have, like ourselves, studied diabetic patients (Matsuda et al, 1983;Sartor et al, 1982) and the question may be raised as to whether the observed variations in drug handling reflect alterations in gastrointestinal motility secondary to autonomic neuropathy complicating the diabetic state (Ikegami et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have measured total radioactivity after giving radiolabelled drug (Balant et al, 1975;Rupp et al, 1972); others have determined immunoreactive glibenclamide (Balant et al, 1977) or employed high performance liquid chromatography (Rogers et al, 1982;WahlinBoll & Melander, 1979) or gas liquid chromatography (Castoldi & Tofanetti, 1979). Use of radioimmunoassay over-estimates glibenclamidederived plasma activity because of crossreactions with hydroxylated metabolites (Pearson, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma glibenclamide concentrations in plasma were estimated by a high pressure liquid chromatographic technique (Rogers et al, 1982) with a minimum level of detection of2 ng ml-'and coefficients of variation of 11.6%, 5.3%, 6.8% at 20 ng ml-', 50 ng ml-l and 100 ng ml-l respectively. Blood glucose was determined by a glucose oxidase method (Trinder, 1969) and plasma immunoreactive insulin was estimated by a commercial radio-immunoassay kit (Lisophase, Lepetit, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…The half-life obtained from intravenous data is between 1.2 and 2.5 h ROGERS et al 1982;NEUGEBAUER et al 1985;SPRAUL et al 1989;McEwEN et al 1982) and between 1.3 and 15 h after oral administration. Most studies obtained values of 1.5-5h (KARTIUNEN et al 1985;NEUGEBAUER et al 19X5;CHALK et al 1986;PEARSON et al 1986;SCHWINGHAMMER et al 1991).…”
Section: D) Eliminationmentioning
confidence: 97%